Defensive role of Nigella sativa against antituberculosis drugs induced renal toxicity. Issue 2 (4th April 2022) - Jaswal, Amita; Sharma, Samta; Uthra, Chhavi; Yadav, Deepa; Shrivastava, Sadhana; Shukla, Sangeeta
Abstract: Drug-induced nephrotoxicity is a common problem in clinical medicine and the frequency of drug-related acute and chronic kidney dysfunction worldwide. One of them is anti-tuberculosis (TB) drugs that cause renal function impairment during TB treatment. Medicinal plants contain bioactive compounds that are capable for treating drug or toxin-induced renal disorders. The aim of the present study was to assess the protective effect of the ethanolic extract of Nigella sativa seeds (NS) against anti-TB drugs (ATDs) induced nephrotoxicity in Wistar albino rats. Rats were treated with ATDs for 12weeks (3 alternative days in a week). Supplementation with 125mg NS/kg, p.o. was administered to the experimental rats for 12weeks (3 alternative days in a week considering next day of ATDs treatment). The results demonstrated that NS treatment protected against renal damage induced by ATDs, as evidenced by the reduction in serum urea, creatinine, uric acid, urea nitrogen levels, pro-inflammatory markers (TNF-α and IL-6), whereas improvement in histological tubular and glomerular damage. In addition, NS enhanced the antioxidant enzyme activity (superoxide dismutase and catalase) and decreased the lipid peroxidation and glutathione level in the kidney. In conclusion, NS could reduce chronic nephritis in ATDs treated group through suppressing inflammation and oxidative stress. It suggests that NS can be used as supplementary preventive and protective drug against kidney injury during anti-TB treatment. Graphical abstract: